2004
DOI: 10.1590/s0103-97332004000400013
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational structure of organic semiconductors: the role of conjugation length

Abstract: Site-selective luminescence spectroscopy (SSL) was employed to resolve the vibracional modes in selfassembled poly(p-phenylene vinylene), PPV. Using Franck-Condon analysis, the PPV spectra can be well described by three effective vibrational modes at 330, 1160 and 1550 cm −1 . As the temperature increases from 4 to 180 K the electron-phonon coupling (S factor) remains constant for the 1550 cm −1 mode while for other lower energy modes the coupling increases monotonically. This trend is consistent with the decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Also, our results agree with recent site-selective luminescence spectroscopy results obtained by Borges et al [20]. In their experimental results, the PPV spectra can be well described by three effective vibrational modes at 330, 1160 and 1550 cm -1 .…”
Section: Ppv Phonon Dispersionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, our results agree with recent site-selective luminescence spectroscopy results obtained by Borges et al [20]. In their experimental results, the PPV spectra can be well described by three effective vibrational modes at 330, 1160 and 1550 cm -1 .…”
Section: Ppv Phonon Dispersionsupporting
confidence: 93%
“…This is the reason that the observed Huang-Rhys factors of the first two modes have an interesting variation with the temperature increasing. If the Huang-Rhys factors are related to the conjugation length, the modes, which involve the entire chain, are the most affected ones [20]. Further details of our obtained results will be published soon in another publication.…”
Section: Ppv Phonon Dispersionmentioning
confidence: 73%
“…With increasing temperature, the Boltzmann distribution moves steadily toward the higher-energy mean value. As such, the low-frequency mode is more sensitive to changes in temperature . It is interesting to note that whereas the low-frequency vibrational mode was absent from emission spectra recorded for both R1 24 and R2 ,10g an averaged hω L of 860 cm -1 had to be included for emission spectra recorded for R3 .…”
Section: Resultsmentioning
confidence: 99%
“…[7,42,63,72,73] In our data S apparent decreases upon increasing the doping level of PCBM up to 50 wt %, which suggests that the effective conjugation length and exciton migration in the PCBM doped MEH-PPV nanoparticles are enhanced. This interpretation contradicts the observed blue shifts of the emission maxima with increasing PCBM doping levels.…”
Section: Franck-condon Analysis Of Single Particle Spectramentioning
confidence: 49%
“…The Huang-Rhys factor has been shown to represent the extent of conjugation and exciton migration in conjugated polymers. [7,42,63,72,73] It can therefore be concluded that the increasing trend of S blue with increasing PCBM doping level indicates reduced exciton migration and increased self trapping of excitons, which corroborates that interchain aggregation is being hindered by the presence of PCBM. In addition, the subsequent decrease of S blue at 75 wt % PCBM doping further supports the notion that phase separation occurs at these high doping levels, leading to conjugated polymer regions in the nanoparticle that are apparently less heavily doped and thus have a larger occurrence of aggregation interactions between polymer chains and consequently enhanced exciton migration properties.…”
Section: Single-particle Ensemblesmentioning
confidence: 70%